DESAIN DIDAKTIS UNTUK MENGATASI LEARNING OBSTACLES MATERI PENJUMLAHAN DAN PENGURANGAN PECAHAN PADA SISWA KELAS IV SD - Mahmud, Muhammad Rifqi (2015)
Penelitianinibertujuanuntukmerancangdesaindidaktis yang dapatmengatasilearning obstacle yang ditemukanpadamateripenjumlahandanpenguranganpecahan di kelas IV SD. Metode yang digunakandalampenelitianiniadalahmetodekualitatifdenganmenggunakanperspektifDidactical Design Research (DDR). Subjekpadapenelitianiniadaduakelompokyaitukelompok yang diberikanTesKemampuanResponden (TKR)awaldankelompok yang mendapatkanpembelajaranmenggunakandesaindidaktissertadiberikan TKR akhir.BerdasarkananalisisdarihasilTKRawaldanhasilwawancarakepadarespondenditemukantigakarakteristiklearning obstacleyaituontogenic obstacle, didactical obstacle, danepistemological obstacle.Selanjutnya, disusundesaindidaktishipotesisdenganmempertimbangkantigaaspekyaitulearning obstacle, learning trajectory siswa, dantheory of didactical situation.Setelahdesaindidaktishipotesisdiimplemantasikandandilakukan TKR akhirmakahasilnyasudahtidakditemukanlagiontogenic obstacle, sedangkandidacatical obstacle danepistemological obstacle masihditemukanhanyakuantitiasnyaberkurang.Berdasarkanhasilanalisisretrospektifdiperolehdesaindidaktisempirik.Padadesaindidaktisempirik, beberaparedaksikalimatharusdirubah agar intervensi guru dapatdikurangidanperubahanbeberapasituasidarilesson designdiubahsesuaidenganresponsiswapadasaatimplementasi. This research aims to design a didactic design that can overcome learning obstacles, which are found in the material addition and subtraction of fractions in fourth grade. The method used in this study is a qualitative method, by using the perspective-Didactical Design Research (DDR). Subjects in this research there were two groups: the group, given Respondent Ability Test (RAT) early, and the groups get to use the design-didactic learning and given final RAT. Based on the analysis of the results of early RAT, and the results of interviews with respondents found three characteristics of learning obstacle, which ontogenic obstacle, didactical obstacles, and epistemological obstacle.Furthermore, structured design-didactic hypothesis by considering three aspects, namely learning obstacle, trajectory learning students, and the theory of didactical situation. After, the design-didactic hypotheses, implemented and conducted RAT end then the result is not found again ontogenic obstacle, while didacatical obstacle and epistemological obstacle is still found only quantity decreases. Based, the results of the retrospective analysis, obtained didactic-empirical design. In the empirical didactic design, some redaction sentence should be modified, so that the teacher intervention can be reduced, and the changes in the situation of lesson design changed in accordance with the student's response at the time of implementation. Keywords: Didactic Design, Learning Obstacle and Fractions